2014
DOI: 10.1016/j.ultrasmedbio.2014.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Application of Ultrasound in the Assessment of Plantar Fascia in Patients With Plantar Fasciitis: A Systematic Review

Abstract: Plantar fasciitis (PFS) is one of the most common causes of heel pain, estimated to affect 10% of the general population during their lifetime. Ultrasound (US) imaging technique is increasingly being used to assess plantar fascia (PF) thickness, monitor the effect of different interventions and guide therapeutic interventions in patients with PFS. The purpose of the present study was to systematically review previously published studies concerning the application of US in the assessment of PF in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 39 publications
1
53
0
1
Order By: Relevance
“…Findings that support the diagnosis of PF include increased proximal plantar fascia thickness and areas of hypoechogenicity ultrasonographically [5,6,13,25,26]. Plantar fascia thickening is a well established feature of PF.…”
Section: Discussionmentioning
confidence: 92%
“…Findings that support the diagnosis of PF include increased proximal plantar fascia thickness and areas of hypoechogenicity ultrasonographically [5,6,13,25,26]. Plantar fascia thickening is a well established feature of PF.…”
Section: Discussionmentioning
confidence: 92%
“…24 A recent SLR on the use of ultrasound in the assessment of PF, found wide variations in methodology, however results indicated that ultrasound is accurate and reliable for assessing plantar fascia thickness, and for monitoring and guiding therapeutic interventions in patients with PF. 25 The primary aims of education, enhance self-management, improve function and decrease pain, were reported by over (206/257, 80%) of physiotherapists as "always" being an aim. All of these primary aims are recommended by NICE for PF.…”
Section: Twomentioning
confidence: 99%
“…It is also used to measure the thickness of plantar fascia, to monitor the Copyright © 2018, Iranian Journal of Radiology. This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited effect of different interventions and to help therapists to follow the effects of therapeutic interventions in patients with plantar fasciitis (5,(14)(15)(16)(17)(18). Additionally, ultrasonography has many other advantages to use, such as being accurate, reliable, non-invasive, and free of radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Plantar fasciitis most commonly occurs up to 2 cm of the heel (6). Measurement stations used to determine plantar fascia thickness varies widely from its insertion at the calcaneal tubercle, until 3 cm distal from its insertion at the calcaneal tubercle (16). According to a study by McNally and Shetty (2010), plantar fasciitis occurs in the insertion, at the calcaneal tubercle, until 1 cm distal to this (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation